Single-molecule FRET unveils induced-fit mechanism for substrate selectivity in flap endonuclease 1 - Rashid, Fahad; Harris, Paul D; Zaher, Manal S; Sobhy, Mohamed A; Joudeh, Luay I; Yan, Chunli; Piwonski, Hubert; Tsutakawa, Susan E; Ivanov, Ivaylo; Tainer, John A; Habuchi, Satoshi; Hamdan, Samir M (eLife, 2017)
Human flap endonuclease 1 (FEN1) and related structure-specific 5’nucleases precisely identify and incise aberrant DNA structures during replication, repair and recombination to avoid genomic instability. Yet, it is unclear how the 5’nuclease mechanisms of DNA distortion and protein ordering robustly mediate efficient and accurate substrate recognition and catalytic selectivity. Here, single-molecule sub-millisecond and millisecond analyses of FEN1 reveal a protein-DNA induced-fit mechanism that efficiently verifies substrate and suppresses off-target cleavage. FEN1 sculpts DNA with diffusion-limited kinetics to test DNA substrate. This DNA distortion mutually ‘locks’ protein and DNA conformation and enables substrate verification with extreme precision. Strikingly, FEN1 never misses cleavage of its cognate substrate while blocking probable formation of catalytically competent interactions with noncognate substrates and fostering their pre-incision dissociation. These findings establish FEN1 has practically perfect precision and that separate control of induced-fit substrate recognition sets up the catalytic selectivity of the nuclease active site for genome stability. When a cell divides it must copy its genetic information, which is found in the form of strands of DNA. Damage to the DNA may lead to cancer or a number of genetic diseases. However, every time a cell divides more than 10 million toxic “flaps” of excess DNA are generated. A protein called flap endonuclease 1 (FEN1) keeps the DNA in good repair by cutting off the flaps in a highly specific and selective manner. Many proteins that interact with DNA are attracted to specific genetic sequences within the DNA strands. However, this is not the case for FEN1 and several other “structure-specific” proteins that help to repair and replicate DNA strands. So how do these proteins select the correct regions of DNA to interact with? Rashid et al. used single-molecule fluorescence measurements to examine how purified FEN1 proteins interact with DNA flaps. The results show that FEN1 can perfectly recognize and correctly remove flaps through a process called “mutual-induced fit”, where the DNA and FEN1 are shaped by each other to produce a highly specific structure. Further work is now needed to examine whether other proteins that are related to FEN1 use a similar process to ensure that they always cut DNA in the same way. More detailed and direct examination of the structure of FEN1 through other experimental methods may also help to reveal how the mutual-induced fit process enables FEN1 to achieve such high levels of precision. This could increase our understanding of how problems with FEN1 and similar proteins lead to different genetic diseases.